Aharonov-Casherjev pojav - Školč, Luka (Matrika, 2021)
When a neutral particle with a magnetic dipole moment encircles an electrostatically charged wire which is parallel to the particle's dipole moment, the particle's wave function acquires a non-trivial topological phase factor. The so-called Aharonov-Casher effect was predicted in 1984 and was later confirmed in different experiments with a precision of at least 4%. In the first part of the article, I guide the reader through the complete derivation of the Aharonov-Casher phase. In the second part, I present two experimental confirmations of the effect and its application in quantum metrology.
Keywords: Aharonov-Casher effect; Aharonov-Casherjev pojav; kvantni merilniki naboja; netrivialna topološka faza; non-trivial topological phase factor; quantum metrology